The global prevalence of social media addiction among university students: a systematic review and meta-analysis - Salari, Nader; Zarei, Hosna; Hosseinian-Far, Amin; Rasoulpoor, Shabnam; Shohaimi, Shamarina; Mohammadi, Masoud (Springer Science and Business Media LLC, 2023)
Aim: The growing popularity of social network sites (SNS) and their benefits have made these networks an integral part of many university students' lives. Excessive use of these networks can lead to behavioral disorders among users, of which the most important currently is addiction. This study was conducted to investigate the global prevalence of social media addiction among university students. Subject and methods In this systematic review and meta-analysis, the PubMed, Web of Science, Jisc Library Hub Discover, Library of Congress, and Google Scholar databases and search engines were systematically searched to identify studies that reported on the global prevalence of social media addiction among the university student population. As part of the search process, no lower time limit was set, and the searches were last updated in April 2022. The heterogeneity of studies was assessed using the I 2 index, and a random-efects model was used for analysis. Data analysis was performed using Comprehensive Meta-Analysis (CMA) software (version 2). Results Following the examination of 51 studies with a sample size of 35,520 students, the pooled global prevalence of social network addiction among university students was found to be 18.4% (95% CI: 14.7–22.6%), with the highest prevalence found in studies conducted in Asia, at 22.8% (95% CI: 18.5–27.6%). Conclusion The results of this study show that the pooled global prevalence of social media addiction among the university student population is 18.4%. Addiction to these social networks among students is an important public health issue and requires specific attention and policies in order to reduce its prevalence among university students.